기관지 결핵 - 박성수; Sung Soo Park; 이정희; Jung Hee Lee (Tuberculosis and respiratory diseases, 1997)
A total of 322 patients with endobronchial tuberculosis (8.1%) out of 3,982 subjects who had a flexible fiberoptic bronchoscopic examination at the Department of Pulmonary Medicine of Hanyang University Hospital between the beginning of March 1982 and the end of April 1996 were included in this study. The peak incidence occurred in the second decade, and the male to female was 1 : 3.0. The barking cough with variable amounts of sputum was the most common chief complaint in 56.9% of the 313 patients. Other complaints included dyspnea, chest pain, fever, hemoptysis, and generalized weakness. Localized wheeze was heard over the chest in 16.9% of the 313 patients. Infiltration/consolidation was the most common roentgenographic finding of the chest in 64.2%. Bronchoscopically, hypertrophy with luminal narrowing was the most common findings in 32.3% of the 322 patients and left main bronchus was the most frequently involved in 24.0%. Using fiberoptic bronchoscopy allows not only substantial meaningful assessment of endobronchial tuberculosis but also makes a differential diagnosis of lung cancer in older patients. We need further evaluations of standard bronchoscopic classification of endobronchial tuberculosis, diagnostic accuracy of endobronchial tuberculosis by PCR, a large prospective study of effects of corticosteroids in endobronchial tuberculosis patients, and appropriate treatment of atelectasis by endobronchial tuberculosis.